Computational pharmacology and computational chemistry of 4-hydroxyisoleucine: Physicochemical, pharmacokinetic, and DFT-based approaches - Ahmad, Imad; Kuznetsov, Aleksey E.; Pirzada, Abdul Saboor; Alsharif, Khalaf F.; Daglia, Maria; Khan, Haroon (Frontiers in Chemistry, 2023)
Computational pharmacology and chemistry of drug-like properties along with pharmacokinetic studies have made it more amenable to decide or predict a potential drug candidate. 4-Hydroxy isoleucine is a pharmaco-logically active natural product with prominent antidiabetic properties. In this study, ADMETLab 2.0 was employed to determine its important drug-related properties. 4-Hydroxy isoleucine is compliant with im-portant drug-like physicochemical properties and pharma giants’ drug-ability rules like Lipinski’s, Pfizer, and GlaxoSmithKline (GSK) rules. Pharmacokinetically, it has been predicted to have satisfactory cell permeability. Blood Brain Barrier permeation may add CNS effects, while a very slight probability of being CYP2C9 substrate exists. None of the well-known toxicities were predicted in silico, being congruent with wet lab results, except for a ‘very slight risk’ for respiratory toxicity predicted. The molecule is non-ecotoxic as ana-lyzed with common indicators such as bioconcentration and LC50 for fathead minnow and daphnia magna. The toxicity parameters identified 4-hydroxy isoleucine as nontoxic to androgen receptors, PPAR-γ, mitochondrial membrane receptors, heat shock elements, and p53. However, out of seven parameters, not even a single toxicophore was found. The density functional theory (DFT) study provided support to the findings obtained from drug-like properties predictions. Hence, it is a very logical approach to proceed further with a detailed pharmacokinetics and drug development process for 4-hydroxy isoleucine.